Upaya Peningkatan Kualitas Kerja Pegawai pada Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung Indragiri Rokan - Mustiqowati Ummul Fithriyyah; Yaumil Hasanah; Khairunsyah Purba (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was carried out at the Indragiri Rokan Watershed and Protected Forest Management Center. The objectives of this study are: 1) To determine the quality of work of employees at the Center for Watershed Management and Protection Forest Indragiri Rokan. 2) To find out efforts to improve the quality of work of employees at the Indragiri Rokan Watershed Management Center. This type of research uses qualitative research with descriptive methods. There are 10 key informants, 7 employees and 3 community members. The results of the study indicate that the quality of work of employees in general is good, when viewed from the work results, work processes and enthusiasm of employees. Because most of the activities are carried out in teams, the weaknesses of each employee can be assisted by employees who have more abilities, namely the team leader. Meanwhile, the indicators of self-potential and employee enthusiasm are suggested to be improved for various reasons. Then there are the four things mentioned above, first: informal training (learning together) among work teams, Second: formal education and training that is carried out on a scheduled basis. Third: ensuring payment of incentives (tunkin and others) that are fair and in accordance with the quality of work of employees. Fourth: ensuring that computer applications (Sikadir, and E-kinerja) can run effectively is an effort to improve the quality of employees at BPDASHL Indragiri Rokan.